GEOCHEMISTRY OF CLINOPYROXENES AND PETROGENESIS OF MANTLE XENOLITHS FROM PLIOCENE BASANITES OF THE DZHILINDA RIVER: (VITIM VOLCANIC FIELD) - Litasov K.D.; Litasov Yu.D.; Mekhonoshin A.S.; Mal'kovets V.G. (My University, 2000)
Three series of peridotite xenoliths from basanites of the Dzhilinda River were analyzed. The trace-element patterns of clinopyroxenes of Iherzolites of series 1 and 2a correspond to low-degree partial melting of the primitive mantle. Poikiloblastic harzburgites composed of minerals with low Mg# and characterized by a dome-like REE patterns in their relict clinopyroxene occur at the depth of garnet facies. Their origin is attributed to reworking of peridotites by percolated melt under high melt/matrix ratio (4-5%). Some peridotites of series 2a are characterized by a depleted composition and contain clinopyroxenes enriched in LREE and depleted in HFSE, which might be due to percolation of small portions of melt. We have established a rare type of interaction of melt with mantle substance producing high-Ti peridotites rich in pyroxenes and spinel (series 3). The high Ti content is indicative of the ilmenite-containing source. The high contents of Cr, Ni, Zn, and V suggest that dunite or harzburgite were initial rocks. The REE patterns in clinopyroxenes indicate a MORE-like composition of the coexisting melt. The Al-augite pyroxenites contain clinopyroxene with trace-element features pointing to their joint origin with low-temperature Cr-diopside pyroxenites. The trace-element patterns of the clinopyroxene megacrysts evidence their origin from fractional crystallization of alkaline basaltic or picrobasaltic melt. Shallow-depth skarn-like clinopyroxenites contain clinopyroxene whose REE pattern has a bend near Sm and show drastic enrichment in LREE. This suggests secondary transformation of rocks under the effect of fluid-rich melt, and these racks were, probably, clinopyroxenite or gabbro with the primary characteristics of MORB.
Keywords: Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен